2018
DOI: 10.20944/preprints201812.0320.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Land Use Land Cover Changes and Their Impact on the Lake Ecosystem of the Central Rift Valley of Ethiopia

Abstract: LULC changes are major environmental challenges in many parts of the world which are adversely affecting ecosystem services. This study was aimed to analyze LULC changes in the ecological landscape of Ethiopia CRV areas from 1985 to 2015. Satellite images were accessed and pre-processing and classification is done. Major LULC types were detected and change analysis was executed. Nine LULC changes were successfully evaluated. The classification result revealed that in 1985, 44.34% of the land was covered with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The frequencies of moderate, severe and extreme drought conditions of the historical and projected periods under the RCP4.5 and 8.5 scenarios for both SPI3 and SPI6 are presented in the Table 2. Note; -Arsi Negele(1), Bulbul(2), Koshe(3), Langano(4), Tora(5) Ziway(6), Assela (7), Degaga(8), Kulmsa (9) Based on standardized precipitation index value calculated for 9 meteorological stations results showed that (1991-1992), (2015-2016) and (2017-2018) were drought year and extremely, severely, and moderately drought condition were observed in this year for historical rainfall data Fig. For projected climatic data in near future (2022, 2029 and 2046) in mid future (2058, 2065 and 2061,2068) and in far future (2099, 2085 and 2099,2083) which were among the drought years for both RCP4.5 and RCP8.5 respectively.…”
Section: Effects On Drought Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies of moderate, severe and extreme drought conditions of the historical and projected periods under the RCP4.5 and 8.5 scenarios for both SPI3 and SPI6 are presented in the Table 2. Note; -Arsi Negele(1), Bulbul(2), Koshe(3), Langano(4), Tora(5) Ziway(6), Assela (7), Degaga(8), Kulmsa (9) Based on standardized precipitation index value calculated for 9 meteorological stations results showed that (1991-1992), (2015-2016) and (2017-2018) were drought year and extremely, severely, and moderately drought condition were observed in this year for historical rainfall data Fig. For projected climatic data in near future (2022, 2029 and 2046) in mid future (2058, 2065 and 2061,2068) and in far future (2099, 2085 and 2099,2083) which were among the drought years for both RCP4.5 and RCP8.5 respectively.…”
Section: Effects On Drought Frequencymentioning
confidence: 99%
“…According to (Elias et al,2019) water bodies especially lakes and associated wetlands of the Central Rift Valley of Ethiopia (CRV) have decreased by 11.57% between the years 1985-2015; the highest turn down, which is 8.89%, was recorded in the years 1995-2015. Therefore, understanding possible future changes in the climate and their impacts on droughts is essential for adaptation and mitigation planning.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Land cover refers to the biophysical characteristics of earth's surface, including the distribution of vegetation, water, soil, and other physical features of the land [6]. Expansion and intensification of agriculture, the growth of urban areas and extraction of timber, and others are likely accelerated the changes in the land-use over the last decades to satisfy the demands of an increasing population [7]. Lake sedimentation is one of the factors reducing life in the lake with the sediments being transferred from the surrounding catchment by rivers and streams draining from different land-uses.…”
Section: Introductionmentioning
confidence: 99%